Investigating the impact of egg white gel structure on peptide kinetics profile during in vitro digestion. (October 2016) - Nyemb-Diop, Kéra; Causeur, David; Jardin, Julien; Briard-Bion, Valérie; Guérin-Dubiard, Catherine; Rutherfurd, Shane M.; Dupont, Didier; Nau, Françoise
Abstract: This study aimed to explore how food structure, in the form of different egg white gel matrices, impacts the peptide kinetics profiles using an in vitro model that simulated digestion in the adult gastrointestinal tract. Four different gel matrices were prepared by heating egg white gel solutions using different combinations of pH and ionic strength. Label-free quantitative peptidomics and statistical analysis of the resulting kinetics profiles were performed. The 3231 identified peptides were distributed in 7 clusters based on "Gel structure × Digestion time" interaction coefficients, indicating that peptide kinetics profiles were greatly influenced by the gel structure. Moreover, the protein within the gel from which the peptides were released was highly significantly correlated with the peptide clusters, demonstrating that the influence of the gel structure varied according to the protein in question. Such findings may have nutritional relevance in vivo as they imply that the peptides reaching the intestine are different according to the initial EW gel structure. Highlights: A focus was made on the "Gel structure × Digestion time" interaction effects. The clustering analysis summarized the 3231 identified peptides into 7 clusters. The egg white gel structural properties influenced the peptide release kinetics. The influence of the egg white gel structure depended on the protein in question. The molecular properties of ovalbumin were related to the peptide release kinetics.